Production and exports of Mexican honey - Pedro Antonio López de Haro; José G. Vargas-Hernández (Atlantic Review of Economics (ARoEc), 2020)
Beekeeping is a very important activity because of its economic, social and ecologic impact. In Mexico, this activity generates revenue, income and employment to people and is closely related with agriculture. The following work is a documentary study that seeks to explain the situation of honey production and exports in Mexico. We show the state of the art on investigations on honey production, differentiating between Apis Mellifera and Melipona bee. We show evidence that the amount of exported honey hasn't significantly risen from 1961 to 2017, however, honey production has risen significantly. This indicates that previously most of the honey production used to be exported, and nowadays consumption has risen in the country. The generation of revenue brought by honey exports has also significantly risen, which indicates an increase in the prices of honey internationally. We conclude that there is potential for the activity and we mention a number of social and governmental proposals to rise honey production and exports in Mexico.
Keywords: F15; Q17; Q21; Q02; 330; Apiculture; honey; production; exports